Фібули із городища на горі Лисуха (знахідки 2016—2018 рр.) - Кармазіна, Л.В. (Археологія і давня історія України, 2019)
Статтю присвячено публікації фібул-застібок із охоронно-рятувальних досліджень Канівською археологічною експедицією городища на горі Лисуха поблизу с. Бучак Канівського р-ну Черкаської обл. у 2016—2018 рр. The paper publishes the collection of fibulae from Lysukha Hillfort obtained during the field exploration from 2016 to 2018. The research was conducted by the archeological team of the Science Research Centre «Protective Archaeology Service of Ukraine»» headed by Dr. Yu. Boltryk. The monument on Lysukha Mountain is located in Middle Dnieper region. The settlement was discovered in 1970 by Dr. E. V. Maksimov. During 1990—2005 the site was explored by Dr. V. O. Petrashenko. The results of the research allow to attribute the site as multi-layered settlements with finds of Late Scythian, Zarubintsy, Chernyakhiv cultures and early Slavic times of the 5th—7th c. AD.